VD_FINDINFO HC / 2010 / 297 vom 23. Februar 2010 - VD Tribunal cantonal (2010)
CONTRAINTE SEXUELLE, PRESSION, VIOL, FIXATION DE LA PEINE, ÉTAT DE FAIT | 189 al. 1 CP, 189 CP, 190 al. 1 CP, 190 CP, 47 CP, 411 let. h CPP, 411 let. i CPP, 447 CPP